What drives sovereign debt portfolios of banks in a crisis context? - Matías Lamas; Javier Mencía (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2019)
We study determinants of sovereign portfolios of Spanish banks over a long time-span, starting in 2008. Our findings challenge the view that banks engaged in moral hazard strategies to exploit the regulatory treatment of sovereign exposures. In particular, we show that being a weakly capitalized bank is not related to higher holdings of domestic sovereign debt. While a strong link is present between central bank liquidity support and sovereign holdings, opportunistic strategies or reach-for-yield behavior appear to be limited to the non-domestic sovereign portfolio of well-capitalized banks, which might have taken advantage of their higher risk-bearing capacity to gain exposure (via central bank liquidity) to the set of riskier sovereign bonds. Furthermore, we document that financial fragmentation in EMU markets has played a key role in reshaping sovereign portfolios of banks. Overall, our results have important implications for the ongoing discussion on the optimal design of the risk-weighted capital framework of banks.
Keywords: G01; G21; H63; 330; Banks' sovereign holdings; sovereign crisis; moral hazard; central bank liquidity; EMU financial fragmentation